Website and Online Store Creation Training for SMEs in Rural Kolam Areas - Muammar Rinaldi; Ahmad Haris Hasanuddin Slamet; Oky Syahputra; Iin Srimulyani; Tina Muhardika Handayani; Henny Purnama Dewi (Outline Journal of Community Development, 2025)
The website and online store training for SMEs in the Kolam Rural Area aimed to enhance the digital capacity of entrepreneurs in marketing their products online. The activity involved 20 SME owners who were taught how to create websites, integrate products into e-commerce platforms, and apply basic digital marketing techniques through social media and SEO. The results of the training showed a significant increase in participants' knowledge of utilizing technology to grow their businesses. Despite challenges related to limited digital infrastructure, participants successfully created and managed their websites and online stores. This training provides a strong foundation for SMEs to expand their market reach and improve their competitiveness. Going forward, further training and improvements in digital infrastructure are essential to ensure the long-term success and sustainability of SMEs in rural areas.